Air carrier liability in case of passenger death or bodily injury under the Montreal Convention - Bratuška, Justīne (Riga Graduate School of Law, 2023)
This bachelor thesis examines the liability of air carriers for passenger injuries or deaths under the Montreal Convention. With the growing importance of air travel globally, the number of passengers is expected to rise, leading to an increased probability of in-flight injuries. The Montreal Convention offers detailed guidelines outlining the obligations of air carriers in such incidents. To be more precise, air carrier's liability for passenger deaths or injuries during different stages of air travel is emphasized in Article 17 of the Convention, which specifically addresses the conditions under which an accident can be attributed to them. However, this Article contains ambiguous terms that require interpretation by the courts, leading to differing understandings and applications in individual cases. The objective of this thesis is to examine the Montreal Convention's provisions, specifically concentrating on the liability of air carriers and any potential limitations that may exist. By examining relevant case law and legal principles, this study seeks to provide a comprehensive understanding of the legal framework governing air carrier liability.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Montreal Convention; Air Carrier Liability